Detailed mapping of faults and fractures along Vestnesa ridge - Roman, Andrei (UiT The Arctic University of Norway, 2017)
This master thesis is focused on studying the Vestnesa Ridge located west of Svalbard. The Vestnesa Ridge is a 100 km long and about 3 km wide sediment drift located on the recently uplifted Svalbard margin. The crest of the ridge is represented with numerous pockmarks with different size, orientation and elongation. High resolution seismic data connected pockmarks with acoustic chimneys and faults located in the subsurface. The Vestnesa Ridge is a gas hydrate province, BSR exists in the study area marking the base of gas hydrate stability zone. Free gas below BSR is migrating towards the crest of the ridge while gas-hydrates act as a cap rock due to reduced permeability. Acoustic chimneys and large faults often penetrate through the gas hydrate stability zone and may provide a permeable vertical conduit for accumulated free gas. Previous works suggested that faults and fractures have an important role in regional fluid flow. Main goal of this master thesis is to map faults and fractures through interpretation of two 3D-seismic datasets and several 2D lines. Seismic datasets covers two areas on west and east of the crest of Vestnesa Ridge. These areas are affected by active fluid expulsion resulting from presence of gas hydrates and moderate tectonic activity related to nearby Molloy Transform Fault and mid ocean spreading ridge. Faults and fractures were mapped using Ant tracking attribute and manual interpretation. Seismic anomalies and morphological features are also interpreted and discussed. Difference between two 3D seismic surveys are observed. Eastern part of the Vestnesa ridge contains more fluid flow features such as chimneys and pockmarks. More faults and fractures are present in the eastern part as well. Fault and fractures in the east tend to be parallel to the crest of the ridge while faults in the western part do not show any preferred orientation. Fault offsets tend to increase with depth leading to a suggestion of several periods of reactivation. Mechanisms controlling formation, reactivation ...